2022
DOI: 10.1371/journal.pgen.1010327
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive forces and resisting spot welds by alternative homolog conjunction govern chromosome shape in Drosophila spermatocytes during prophase I

Abstract: The bivalent chromosomes that are generated during prophase of meiosis I comprise a pair of homologous chromosomes. Homolog pairing during prophase I must include mechanisms that avoid or eliminate entanglements between non-homologous chromosomes. In Drosophila spermatocytes, non-homologous associations are disrupted by chromosome territory formation, while linkages between homologous chromosomes are maintained by special conjunction proteins. These proteins function as alternative for crossovers that link hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Do these dots mark the location of autosomal homolog conjunction, or might there be additional SUM complexes at other locations below the limit of detection that contribute to conjunction as well? Recent cytological analyses of meiotic quadrivalents in spermatocytes heterozygous for autosomal translocations have indicated that autosomal homolog conjunction is spatially constrained to dot-like chromosomal locations [ 36 ]. The spatial control of autosomal homolog conjunction in spermatocytes appears to be analogous to that of canonical crossovers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Do these dots mark the location of autosomal homolog conjunction, or might there be additional SUM complexes at other locations below the limit of detection that contribute to conjunction as well? Recent cytological analyses of meiotic quadrivalents in spermatocytes heterozygous for autosomal translocations have indicated that autosomal homolog conjunction is spatially constrained to dot-like chromosomal locations [ 36 ]. The spatial control of autosomal homolog conjunction in spermatocytes appears to be analogous to that of canonical crossovers.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial control of autosomal homolog conjunction in spermatocytes appears to be analogous to that of canonical crossovers. As a rule, a single restricted region within the euchromatic portion of each autosomal chromosome arm is linked by AHC protein assemblies to its homologous region [ 36 ]. Thus, AHC positions might be controlled by processes analogous to crossover interference.…”
Section: Discussionmentioning
confidence: 99%
“…During chromosome condensation at the onset of the first meiotic division (M I), the sub-nucleolar SUM foci coalesce into a single large dot at the XY chromosome (chr) pairing site [ 20 , 22 ]. On autosomal bivalents, the SUM proteins are present in much smaller dots that are not necessarily always detectable above background [ 20 , 22 , 23 , 27 ]. The number of SUM dots on autosomal bivalents appears to be restricted to around one or two per bivalent at the start of M I [ 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…On autosomal bivalents, the SUM proteins are present in much smaller dots that are not necessarily always detectable above background [ 20 , 22 , 23 , 27 ]. The number of SUM dots on autosomal bivalents appears to be restricted to around one or two per bivalent at the start of M I [ 23 , 27 ]. Their chromosomal localization is presumably distinct in each spermatocyte, as genetic analyses have revealed a wide-spread distribution of meiotic conjunction potential throughout the euchromatic regions rather than dedicated invariant autosomal conjunction sites [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation